Sistem Pendukung Keputusan Penentuan Rating Acara pada Radio Karysma FM. Boyolali - Sukma Mustika Aji, Muhammad Hasbi, Sri Hariyati Fitriasih (Jurnal Ilmiah SINUS, 2013)
The research report titled "Determination of Decision Support Systems Rating Event In Karysma Fm Radio Boyolali" karysma fm radio Boyolali help to determine the rating the show so it can determine advertising rates accordingly. To achieve maximum benefit based on advertising rates are adjusted with a rating event, we used Multiple Linear Regression method. Multiple Linear Regression methods were used to predict Y if all the independent variables are known. In this case study, the method used to determine the size of the rating event. While the event rating was measured by segmenting the event. The system uses PHP as the programming language and the MySQL database as a store, where there are 8 tables that airtime, program type, type of music, advertising rates, users, analysis, coefficients, and graphic rating. The research is expected to assist in determining the rating event marketing to support decision-making advertising tariff. The application program only helps to provide input to the marketing, but the decision remains in the hands of the marketing. Keywords : Decision Support Systems, rating event, FM Radio, marketing, tariff